2018
DOI: 10.1016/j.apsb.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The application of CAR-T cell therapy in hematological malignancies: advantages and challenges

Abstract: Chimeric antigen receptor T cell (CAR-T cell) therapy is a novel adoptive immunotherapy where T lymphocytes are engineered with synthetic receptors known as chimeric antigen receptors (CAR). The CAR-T cell is an effector T cell that recognizes and eliminates specific cancer cells, independent of major histocompatibility complex molecules. The whole procedure of CAR-T cell production is not well understood. The CAR-T cell has been used predominantly in the treatment of hematological malignancies, including acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
166
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(173 citation statements)
references
References 146 publications
(266 reference statements)
0
166
0
7
Order By: Relevance
“…Indeed, clinical trials of the last few years have demonstrated a high effi cacy of CAR T therapy in the treatment of refractory B cell neoplasms. Large scale clinical trials, which have granted approval for the two products based on CD19 specific CAR T, demonstrated sustained efficacy of these products in the treatment of malignant B cell neoplasms (B ALL, non Hodgkin lymphoma) resulting in a com plete recovery in 70 90% patients with relapsed B ALL [28,29].…”
Section: Clinical Application Of Car T Therapymentioning
confidence: 99%
“…Indeed, clinical trials of the last few years have demonstrated a high effi cacy of CAR T therapy in the treatment of refractory B cell neoplasms. Large scale clinical trials, which have granted approval for the two products based on CD19 specific CAR T, demonstrated sustained efficacy of these products in the treatment of malignant B cell neoplasms (B ALL, non Hodgkin lymphoma) resulting in a com plete recovery in 70 90% patients with relapsed B ALL [28,29].…”
Section: Clinical Application Of Car T Therapymentioning
confidence: 99%
“…The CD19 CAR-T cells of the clinical trial are summarized in Table 2. Clinical studies at several different institutions have used CD19 CAR-T cell therapy in children and adults with recurrent B cell acute lymphoblastic leukemia (B-ALL), B cell non-Hodgkin's lymphoma (B-NHL), and chronic lymphocytic leukemia (CLL), and these studies showed high antitumor treatment efficacy [77,78]. As of August 2017, there were approximately 200 clinical trials involving CAR-T cells worldwide [79].…”
Section: Preclinical Studies Of Car-t Cell Immunotherapymentioning
confidence: 99%
“…Antijen tanıyan bölge, tümör ilişkili antijene karşı tipik bir tek zincirli değişken fragman (scFv) antikorudur. 2 T-hücre sinyal domaini ise, T-hücre aktivasyon domaini (CD3zeta) ve ko-stimülatör domainden (CD28, CD134 (OX40) veya CD137 (4-1BB) gibi) oluşmaktadır. Reseptörün aralayıcı (hinge/spacer) ve transmembran bölgeleri ise ekstraselüler antijen tanıyan domaini, sitoplazmik sinyalizasyon domainine bağlamaktadır (Şekil 1).…”
unclassified
“…İnfüze edilen CAR-T-hücreler dolaşımda medyan 30-300 gün kalırlar. 2,[6][7][8][9][10] CAR-T HÜCRE TEDAVİSİNİN YAN ETKİLERİ…”
unclassified